Ecological Pressures In Pusong Harbour: Integrated Assessment Of Water Quality, Nutrient Enrichment, And Pollution Index - Cut Meurah Nurul 'Akla; Malik Pajar Lubis; Erniati Erniati; Rian Firdaus; Imamshadiqin Imamshadiqin; Imanullah Imanullah (Jurnal Kelautan, 2025)
ABSTRACTPusong Harbor in Lhokseumawe City doubles as a center for fisheries activities as well as a habitat for marine biota, making it vulnerable to pollution pressure from anthropogenic activities. This study aims to assess water quality through the analysis of physico-chemical parameters, nutrient content (nitrate and phosphate), pollution index, and spatial variation patterns using a multivariate approach. Measurements were taken at three stations representing the locations of boat moorings, settlements, and fish farms. The measurement results showed that basic parameters such as salinity (32-33‰), pH (7.5-8.0), dissolved oxygen (5.8-6.3 mg/L), and BOD (1.6-3.6 mg/L) were still within the quality standard range, but the brightness level was low (0.8-0.9 m) and the phosphate concentration was very high (7.2-10.1 mg/L), exceeding the quality standard by hundreds of times. The pollution index based on the harbor quality standard showed a Slightly polluted (PI = 1.09-1.11), but based on the marine biota quality standard it was classified as "heavily polluted" (PI = 10.3-10.9). PCA analysis identified phosphate and BOD as the dominant factors differentiating water quality, while temperature, salinity and DO were more reflective of natural conditions. Cluster analysis showed that stations 1 and 3 were similar, while station 2 differed significantly due to local pressures. This finding confirms the serious ecological pressures in the harbor area, especially due to excessive nutrient loads, and calls for pollutant control strategies and continuous monitoring to maintain the sustainability of coastal ecosystems. The study highlights the urgent need to address nutrient-driven pollution in Pusong Harbor, where phosphate concentrations exceed marine biota standards by hundreds of times despite most basic water parameters remaining within acceptable limits. This excessive nutrient load poses a serious threat of eutrophication, habitat degradation, and loss of biodiversity in a harbor that supports both fisheries activities and critical marine life. By integrating physico-chemical measurements, nutrient analysis, and multivariate statistics, the research identifies phosphate and BOD as key pollution drivers and reveals spatial variation linked to human activities. These findings provide evidence-based guidance for local management and policy, calling for targeted pollutant control and continuous monitoring to protect coastal ecosystems. The multivariate framework also offers a replicable approach for similar small-harbor environments across Southeast Asia.Keywords: water quality, pollution index, PCA, cluster, nutrients, Pusong Harbour